ALAM DAN KESEHATAN MENTAL - Febrita, suci Shawmy; desmita, desmita (Batanang : Jurnal Psikologi, 2024)
Mental health is an important aspect of human well-being in living life, but is often neglected. In human life, of course, there is pressure (stress) for humans to move, good stress is certainly useful for human survival. If bad or excessive stress causes people to experience mental health disorders such as anxiety and depression. The era of technological and scientific development not only helps make human tasks easier but also increasingly separates humans from nature. The relationship between humans and nature is harmonious, nature provides every need for human life and nature needs to be protected and cared for by humans to create a good ecosystem. If there is no connection or connectivity between humans and nature, it will certainly cause humans to experience bad stress and even physical and psychological illnesses. Humans use various methods to reduce stress both pharmacologically and non-pharmacologically. Natural therapy is a non-pharmacological or alternative way to reduce stress. Nature can have a positive effect on human mental health. The research method used is a literature study, where the data sources come from books, articles, journals, research reports, and electronic media. The results of this research are that nature therapy can help human mental health with various activities that can be done in nature, such as walking in the forest slowly without sound, inhaling the aroma of the forest, shouting activities, observing animals around, meditation activities, soaking in the water. river, activities to hear the sound of water, water stone therapy activities, tea-drinking activities, tree-hugging activities, and art therapy (drawing or painting). These activities can help increase positive thoughts, self-acceptance, feelings of health, calm, joy, and prosperity and reduce levels of stress anxiety, and other mental pressure